Correlation of Ultrasonography and MRI in Prenatal Diagnosis of Lobar Holoprosencephaly - Evrim Erdemoğlu; Mansur Kamacı (Medical Network, 2008)
Prenatal diagnosis for alobar holoprosencephaly, is not difficult while for semilobar and lobar forms itmay be difficult. We present and discuss prenatal ultrasonographic and magnetic resonance imaging features of lobar holoprosencephaly in a 29 weeks-old fetus diagnosed prenatally. A nineteen years-old primigravid woman was referred with diagnosis of hydrocephalus. In ultrasonographic examination, lateral ventricles and cisterna magna were dilated, but absence of cavum septum pellucidum excluded the diagnosis of hydrocephalus. B mode examination of coronal and transverse sections of fetal brain revealed a cystic cavity of partly fused frontal horns between the two hemispheres in the anterior part of skull, and thalamic fusion. However, frontal horns were developed and discernible. Midline echo, lateral ventricles and third ventricle were observed. It was not possible to examine sagital planes of fetal brain by ultrasonography. Ultrasonographic diagnosis was lobar holoprosencephaly, which was then confirmed by fetal MRI. Ultrasonographic and MRI correlation was assessed. A detailed ultrasonographic evaluation is the primary examination method of obstetrician and it may help to diagnose and grade holoprosencephaly. Besides its correlation with prenatal MRI is good.